Results of Laboratory Testing for Immersion, Envelopment, and Horizontal Stiffness on Turn and Position Devices to Manage Pressure Injury. (October 2020) - Call, Evan; Tanner, Laurel; Cheney, Adam; Rappl, Laurie; Santamaria, Nick; Gefen, Amit; Oberg, Craig
ABSTRACT: Background: A continuing complication, pressure injuries are due to sustained mechanical loading and tissue deformations, which can then be exacerbated by additional intrinsic and extrinsic risk factors. Although support surfaces are designed to mitigate risk factors for pressure injuries, the presence of a turn and position device (TPD) between the patient and support surface may interfere with how support surfaces affect these risk factors. Objective: Report the use of the NPIAP's S3I standard test methods to characterize the performance of a support surface when used in conjunction with three different TPDs. Design: Laboratory testing compared three TPDs for Immersion, Envelopment, and Horizontal Stiffness in each of five surface combinations. Main outcome measure: Immersion test measures how far mannequin indenter immerses into surface. Envelopment test measures immersion and pressure distribution with hemispherical-indenter with mounted sensor rings. Horizontal Stiffness test measures the shear modulus of the support surface with epicondyle indenter. Main results: For the specific TPDs tested here, the one with an adjustable integrated air bladder improved rather than compromised both the envelopment and the immersion of the support surface alone. Additionally, this TPD provided potential protection against sliding and the associated frictional shear forces. Conclusions: This paper describes how TPDs should perform in order to help establish which features are needed in a new medical device of this type. Laboratory testing demonstrates it is possible to improve performance of a support surface by applying a TPD as an add-on, thus relieving tissue deformation exposure through more effective pressure redistribution.